Accuracy of Automated Sysmex XN-1OOO Haematology Analyzer to Diagnose Malaria Keeping Microscopy as Gold Standard - Dur-e Nayyab; Khan, Khalid; Muhammad Ibrahim; Mahabat Khan, Hamed; Arif, Sana; Riaz, Huma (Indus Journal of Bioscience Research, 2025)
Objective: To assess the diagnostic accuracy of the Sysmex XN-1000 haematology analyser for malaria detection, using peripheral blood smear microscopy as the reference standard. Methods: A cross-sectional diagnostic accuracy study that included 185 blood samples obtained from patients undergoing routine complete blood count testing. Samples were taken by using non-probability consecutive sampling at the Haematology Department of PGMI/Hayatabad Medical Complex, Peshawar for the duration of three months from March 21, 2025 to June 20, 2025. Each sample was evaluated by using the Sysmex XN-1000 analyser with particular assessment of malaria-associated scattergram abnormalities. Paired peripheral blood smears were prepared and independently examined by a consultant haematologist who was blinded to analyser results. Direct comparisons with microscopic findings were used to compute diagnostic indices. Results: 68 out of 185 samples confirmed malarial parasites in microscopy, suggesting a prevalence of 36.8%. The Sysmex XN-1000 analyser showed a 92.65% sensitivity and 89.74% specificity. The 95.45% negative predictive value, indicates a strong ability to exclude malaria when analyser flags were absent. The overall diagnostic accuracy was 90.81%. Conclusion: As a screening tool for malaria, the Sysmex XN-1000 haematology analyzer demonstrates a strong diagnostic accuracy and high sensitivity. In regions where malaria is endemic, its regular application may help identify suspected cases promptly. It further expedites the confirmation tests and starts the management on time, even though it does not substitute for microscopy.